2022
DOI: 10.3390/coatings12101583
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Conductive Indium Zinc Oxide Films: Temperature and Oxygen Dependences of the Electrical and Optical Properties

Abstract: Achieving high-efficiency optoelectronic devices often requires the development of high transparency in the extended range and high-conductivity materials, which can be ensured by the high mobility of charge carriers being used as the electrode. Among the candidate materials, transparent conductive indium zinc oxide (IZO) has attracted significant interest because of its superior electron mobility (5−60 cm2/V·s) and the thermal stability of its structure. In this study, the IZO films were deposited by the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Our earlier studies of the influence of technological conditions of RF sputtering deposition on the functional properties of IZO films showed that the optimal substrate temperature for the deposition of amorphous IZO films is 100 °C [ 29 ]. Upon sputtering in a pure argon medium, the transport of carriers in the IZO film is characterized by high free electron concentration n > 7 × 10 20 cm –3 and low resistivity ρ of 3.35 × 10 −4 Ω·cm, while when using a Ar/O 2 (0.4%) gas mixture as a working gas, the carrier concentration decreased down to 2.7 × 10 20 cm −3 , but the Hall mobility µ increased by 50% to a value of 39.2 cm 2 /V·s, which in combination resulted in a not so dramatic increase in resistivity ρ up to 5.5 × 10 −4 Ω·cm (see the Supplementary Materials (SM), Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our earlier studies of the influence of technological conditions of RF sputtering deposition on the functional properties of IZO films showed that the optimal substrate temperature for the deposition of amorphous IZO films is 100 °C [ 29 ]. Upon sputtering in a pure argon medium, the transport of carriers in the IZO film is characterized by high free electron concentration n > 7 × 10 20 cm –3 and low resistivity ρ of 3.35 × 10 −4 Ω·cm, while when using a Ar/O 2 (0.4%) gas mixture as a working gas, the carrier concentration decreased down to 2.7 × 10 20 cm −3 , but the Hall mobility µ increased by 50% to a value of 39.2 cm 2 /V·s, which in combination resulted in a not so dramatic increase in resistivity ρ up to 5.5 × 10 −4 Ω·cm (see the Supplementary Materials (SM), Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A home-made RF magnetron sputtering setup was used to deposit the N × [ n -ZnO/µ-ZnO] multilayers (MLs) at working gas pressure of 0.5 Pa from 2-inch IZO disk targets with In 2 O 3 /ZnO weight ratio of 9:1 onto glass substrates heated to 100 °C. A detailed description of the experimental setup is given in [ 29 , 32 ]. Switching between the n -IZO and µ-IZO deposition modes was carried out by controlled periodic change in the composition of the working gas from pure Ar to an Ar/O 2 (0.4%) gas mixture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decades, transparent conducting oxides (TCOs) have been considered attractive materials in different areas due to their high electrical conductivity and large transparency in the visible and near-infrared regions of the electromagnetic spectrum [1][2][3][4]. TCOs are used in a wide variety of devices, e.g., in solar cells, light-emitting diodes (LEDs), organic light-emitting diodes (OLEDs), liquid crystal displays, touch screens, photothermal conversion systems, and intelligent windows [5][6][7][8][9][10][11]. The sheet resistance required for a thin transparent electrode strictly depends on the type of application where it is implemented.…”
Section: Introductionmentioning
confidence: 99%